First Amendment Cases, Controversies, and Contexts - Robson, Ruthann (Open textbook library., 2019)
This Casebook (Second Edition, December 2019) is intended to be used in an upper-division course covering the First Amendment to the United States Constitution. Its 14 chapters are substantially the same length, with the exception of Chapter One, the introduction, and Chapters Eleven and Twelve which in combination are the usual length. It is intended for 13 or 14 week semester that meets once or twice per week. Each Chapter contains a “Chapter Outline” at the beginning for ease of reference. The Casebook is organized with the Speech Clauses as Part One and the Religion Clauses as Part Two. Unlike many other courses, there is no accepted organizational scheme within these broad areas. As the Introduction notes, First Amendment doctrine, especially within freedom of speech, presents a varied and haphazard landscape. The Casebook follows a scheme that has proven effective in Professor Robson’s years of teaching the course to hundreds of students. The selection of cases tends toward the most recent and these tend to be less heavily edited. These recent cases often contain extended discussions of earlier cases that are not included in the Casebook.